Brain arterial aging and its relationship to Alzheimer dementia. (19th April 2016) - Gutierrez, Jose; Honig, Lawrence; Elkind, Mitchell S.V.; Mohr, Jay P.; Goldman, James; Dwork, Andrew J.; Morgello, Susan; Marshall, Randolph S.
Abstract : Objective: To test the hypothesis that brain arterial aging is associated with the pathologic diagnosis of Alzheimer disease (AD). Methods: Brain large arteries were assessed for diameter, gaps in the internal elastic lamina (IEL), luminal stenosis, atherosclerosis, and lumen-to-wall ratio. Elastin, collagen, and amyloid were assessed with Van Gieson, trichrome, and Congo red staining intensities, and quantified automatically. Brain infarcts and AD (defined pathologically) were assessed at autopsy. We created a brain arterial aging (BAA) score with arterial characteristics associated with aging after adjusting for demographic and clinical variables using cross-sectional generalized linear models. Results: We studied 194 autopsied brains, 25 (13%) of which had autopsy evidence of AD. Brain arterial aging consisted of higher interadventitial and lumen diameters, thickening of the wall, increased prevalence of IEL gaps, concentric intima thickening, elastin loss, increased amyloid deposition, and a higher IEL proportion without changes in lumen-to-wall ratio. In multivariable analysis, a high IEL proportion (B = 1.96, p = 0.030), thick media (B = 3.50, p = 0.001), elastin loss (B = 6.16, p < 0.001), IEL gaps (B = 3.14, p = 0.023), and concentric intima thickening (B = 7.19, p < 0.001) were used to create the BAA score. Adjusting for demographics, vascular risk factors, atherosclerosis, and brain infarcts, the BAA score was associated with AD (B = 0.022, p = 0.002). Conclusions: Aging of brain large arteries is characterized by arterial dilation with a commensurate wall thickening, elastin loss, and IEL gaps. Greater intensity of arterial aging was associated with AD independently of atherosclerosis and brain infarcts. Understanding the drivers of arterial aging may advance the knowledge of the pathophysiology of AD.